2019
DOI: 10.1097/ftd.0000000000000581
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Trough Concentrations and High Vancomycin Minimum Inhibitory Concentration in Methicillin-Sensitive Staphylococcus aureus From Hemodialysis Patients in Brazil

Abstract: Background: The empiric antimicrobial therapy for bacteremia of long-term hemodialysis (HD) outpatients is currently based on the combination of vancomycin and gentamicin because of the high frequency of isolated Staphylococcus species. The vancomycin trough level range from 15 to 20 mcg/mL is expected for therapeutic success against methicillin-resistant Staphylococcus aureus with vancomycin minimum inhibitory concentration (MIC) ≥1.0 mcg/mL. Despite the availability of clinical practice guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In the past, we used the vancomycin trough concentration (C min ) as a therapeutic target to optimize the vancomycin dosage regimen. However, some studies have reported that the C min was not associated with the success of infection treatment 13–15 . The Infectious Diseases Society of America (IDSA) Clinical Practice Guidelines recommend the area under the serum concentration time curve over 24 h/minimum inhibitory concentration ratio (AUC 0–24 /MIC) >400 as the ideal pharmacodynamic index to guide vancomycin dose adjustment 16 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, we used the vancomycin trough concentration (C min ) as a therapeutic target to optimize the vancomycin dosage regimen. However, some studies have reported that the C min was not associated with the success of infection treatment 13–15 . The Infectious Diseases Society of America (IDSA) Clinical Practice Guidelines recommend the area under the serum concentration time curve over 24 h/minimum inhibitory concentration ratio (AUC 0–24 /MIC) >400 as the ideal pharmacodynamic index to guide vancomycin dose adjustment 16 …”
mentioning
confidence: 99%
“…However, some studies have reported that the C min was not associated with the success of infection treatment. [13][14][15] The Infectious Diseases Society of America (IDSA) Clinical Practice Guidelines recommend the area under the serum concentration time curve over 24 h/minimum inhibitory concentration ratio (AUC 0-24 /MIC) >400 as the ideal pharmacodynamic index to guide vancomycin dose adjustment. 16 Therefore, the purpose of this study was to compare the vancomycin CL in critically ill infants with augmented renal clearance and with normal renal function, and to optimize the dosage regimen for infants with augmented renal clearance using AUC 0-24 /MIC.…”
mentioning
confidence: 99%